Impact of leaves of different mulberry genotypes on nutritional efficiency of conversion parameters of silkworm, Bombyx mori L. - Islam, Tajamul; Bhat, Shabir Ahmad; Qadir, Jasmeena; Malik, Firdous Ahmad; Wani, Shabir Ahmad; Khan, Farooq Ahmad; Mir, Shakeel Ahmad; Nazir, Nageena (Journal of Scientific Agriculture, 2024)
The silkworm, Bombyx mori, is a domesticated insect widely used to produce silk worldwide for human consumption. B. mori is a monophagous insect that feeds on nutritious mulberry leaves to produce silk. The efficiency of conversion of leaves to larval biomass by silkworm larva largely depends upon the type of silkworm breed/hybrid and the quality of mulberry leaves fed to them. The silkworms having good efficiency of conversion of leaves perform better in larval growth and silk gland development, which finally leads to enhanced silk production. In the current research work, the highest efficiency of conversion of ingesta to larva (28.608%) and efficiency of conversion of digesta to larva (51.527%) were found in Goshoerami fed silkworm batch which differed significantly from other varieties.